Chronic pre-treatment with memantine prevents amyloid-beta protein-mediated long-term potentiation disruption. - ANWYL, ROGER (My University, 2013)
Previous studies indicate that memantine, a low-affinity N-methyl-D-aspartate receptor antagonist, exerted acute protective effects against amyloid-β protein-induced neurotoxicity. In the present study, the chronic effects and mechanisms of memantine were investigated further using electrophysiological methods. The results showed that 7-day intraperitoneal application of memantine, at doses of 5 mg/kg or 20 mg/kg, did not alter hippocampal long-term potentiation induction in rats, while 40 mg/kg memantine presented potent long-term potentiation inhibition. Then further in vitro studys were carried out in 5 mg/kg and 20 mg/kg memantine treated rats. We found that 20 mg/kg memantine attenuated the potent long-term potentiation inhibition caused by exposure to amyloid-β protein in the dentate gyrus in vitro. These findings are the first to demonstrate the antagonizing effect of long-term systematic treatment of memantine against amyloid-β protein triggered long-term potentiation inhibition to improve synaptic plasticity.
PUBLISHED
Keywords: Physiology